Pendampingan Implementasi Pembelajaran Mendalam Di Madrasah Ibtidaiyah - Dian Ayu Syafitri; Saniyyatul Khadijah; Muhamad Ilham Hanafi; Ahmad Isroil (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2026)
Basic education plays a strategic role in shaping the intellectual, emotional, and spiritual foundations of students. MI Roudlotut Tholibin Warukulon implements a Deep Learning approach as an effort to improve the quality of education in line with the Independent Curriculum. Deep Learning in the educational context is defined as an in-depth learning approach that emphasizes holistic, reflective, and meaningful conceptual understanding, rather than as artificial intelligence technology. Initial investigations indicate that this approach has the potential to improve students' conceptual understanding and critical thinking skills. However, its implementation still faces challenges such as curriculum readiness, teacher competency, and limited supporting facilities. As a follow-up, a two-day mentoring activity was conducted, focusing on strengthening deep learning concepts and developing learning instrument skills. This community service activity aims to strengthen deep learning concepts and develop learning instrument skills. This activity uses the Service Learning method with stages of investigation, team formation, preparation, action, reflection, and demonstration. This service activity has resulted in a paradigm shift in learning towards a more active, reflective, collaborative, and enjoyable approach through the integration of Meaningful Learning, Mindful Learning, and Joyful Learning.